Are Environmentally Related Taxes Effective? - Sebastian Miller; Mauricio Vela (Inter-American Development Bank (IDB), 2013)
This paper focuses on the question of whether the magnitude of long-established environmentally related taxes (ERT) is related to countries environmental performance. While environmental taxes efficiencies have previously been discussed, those taxes contribution to reducing pollution and improving environmental quality has not been fully explored. This paper therefore analyzes the effectiveness of environmental taxes by examining the environmental performance of 50 countries from all regions in association with the amount of revenues from environmentally related taxes each country collects. Using a cross-section regression and a panel dynamic regression, the paper finds that countries with higher revenues from these types of taxes also exhibit higher reductions in CO2 emission, PM10 emissions, and energy consumption and production from fossil sources.
Keywords: H23; Q53; Q58; 330